Lipoprotein(a) as a predictor of mortality in hospitalised patients with ischaemic heart disease - Loh, Wann Jia; Koh, Xuan Han; Yeo, Colin; Ruan, Xucong; Chai, Siang Chew; Chow, Weien; Aw, Tar Choon; Heng, Chew Kiat; Foo, Roger (Frontiers in Endocrinology, 2025)
BackgroundElevated Lipoprotein(a) [Lp(a)] increases the risk of cardiovascular disease and mortality in population studies but reports of whether elevated Lp(a) concentration predicts mortality in hospitalised patients with cardiovascular disease are still lacking and conflicting.AimTo investigate whether elevated Lp(a) predicted cardiovascular outcomes in patients with ischaemic heart disease (IHD) admitted to hospital.MethodsSerum Lp(a) concentrations were measured in 520 consecutively recruited patients admitted to hospital with IHD, half of whom had an acute myocardial infarction. Patients with elevated Lp(a) at baseline were compared with patients with non-elevated Lp(a). In this observational prospective cohort study, multivariable Cox proportional hazards regression was used to assess the association of baseline Lp(a) with hazard rates (HR) of mortality and major adverse cardiovascular events (MACE).ResultsDuring the 2-year follow-up period, 14.6%, 8.5%, and 49.2% of patients had all-cause mortality, cardiovascular mortality, and MACE respectively. Median age was 63.5 years, 82.3% were male and the median Lp(a) was 35.2 nmol/L. Multivariable Cox regression showed baseline Lp(a) ≥70 nmol/L was associated with increased risk of all-cause mortality (HR 1.97 [1.20-3.22], p=0.007) and cardiovascular mortality (HR 2.01 [1.06-3.82], p=0.033), but was not statistically significant for MACE (HR 1.29 [0.98-1.7], p=0.067). Higher natural log-transformed Lp(a) concentrations predicted all-cause mortality (HR 1.25 [1.01-1.58], p=0.042) but not for cardiovascular mortality or MACE.ConclusionIn a multi-ethnic Asian patient cohort, elevated Lp(a) concentrations ≥70 nmol/L at hospitalization positively predicted cardiovascular and all-cause mortality in patients with ischaemic heart disease. Our findings support guidelines’ recommendation for routine evaluation of Lp(a) in all patients at high cardiovascular risk.